Esophageal Perforation with Unilateral Fluidothorax Caused by Nasogastric Tube. (10th October 2016) - Mileder, Lukas P.; Müller, Martin; Reiterer, Friedrich; Pilhatsch, Alexander; Gürtl-Lackner, Barbara; Urlesberger, Berndt; Raith, Wolfgang
Abstract : Preterm infants are highly susceptible to injuries following necessary and often life-saving medical interventions. Esophageal perforation is a rare, yet serious complication that can be caused by aerodigestive tract suction, endotracheal intubation, or nasogastric tube placement. We present the case of a neonate born at 23 weeks plus three days of gestation with chest radiography showing malposition of the nasogastric feeding tube and massive right-sided effusion of Iopamidol in the pleural cavity due to esophageal perforation. In addition, the article summarizes common signs and symptoms associated with esophageal perforation in infants and discusses diagnostic approaches.